Identifying useful learning tasks and web-based instruction in facilitating learning of Chinese characters among non native Mandarin students / Ong Sheau Fen … [et al.] - Ong, Sheau Fen; Er, Ann Nah; Marimuthu, Rasaya; Liaw, Shun Chone (Universiti Teknologi MARA, Pulau Pinang & Pusat Penerbitan Universiti (UPENA), 2015)
In the learning of elementary Mandarin, students are usually required to attend face to face lecture in class, allocate self learning time to do revision as well as assignments, and learn beyond the classroom lessons by referring to resources from the library and Internet. To make the learning in these three situations more interesting and successful, students can utilize web-based instruction (WBI). In order to provide WBI that is tailored to students’ needs, the lecturers should arm themselves with the knowledge of constructing a WBI. The first step to the design and construction of a WBI for learning Chinese characters is to develop and identify a set of clear and easy to understand instructions. Hence a survey was carried out to identify the instructions that students find easy to understand, use and follow in their use of WBI to facilitate the learning of Chinese Characters. A set of 4-point Likert scale questionnaire was developed based on 4 popular web sites that teach Chinese characters. These web sites were selected based on several criteria. The respondents were brought to computer lab and asked to browse the selected web sites to learn Chinese Characters. After the learning, respondents were required to answer the questionnaire to choose the instructions they like. The data collected were analyzed using SPSS 17.0. The mean scores of the questionnaires items were analyzed. The results show that the tasks for Learning the Chinese characters in accordance to the sequence of task A to task D (task A to D were stated in the section of result and analysis) were considered useful by the students. Besides, to answer the second research question, 10 web-based instructions that have the highest mean score were identified as the respondents’ preferred instructions. The instructions that were compiled, however, may only be suitable for Malay students and not for others.